Disgorgement Fund untuk mewujudkan Corrective Justice sebagai upaya perlindungan hukum kepada investor di pasar modal - Marsinta Simanjuntak (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
Disgorgement Fund is the repayment of funds obtained through illegal or unethical business transactions, imposed on violators by courts. Legal protection for capital market investors in Indonesia is not yet effective and optimal. There is no easy way to claim compensation for losses in the capital market because investors consider losses as an investment risk. This article aims to analyze the implementation of disgorgement funds and disgorgement fund practices to realize corrective justice as an effort to protect the law for capital market investors in Indonesia. The method used is normative legal research, using primary and secondary legal sources. Data analysis techniques use conceptual methods and statutory approach methods. The results of the analysis show that OJK issued disgorgement fund regulations as an effort to improve investor protection and law enforcement in the capital market through POJK No. 65/POJK.04/2020 and SEOJK No. 17/SEOJK.04/2021. The regulation of the disgorgement fund mechanism still needs improvement to prevent violators from enjoying illegal profits, recover investors’ losses, and take preventive measures against future violations. The Directorate of Sanctions Determination and Capital Market Grievances at OJK emphasizes that the order for disgorgement of funds is not a lawsuit from the investor through remedial action, aligning with the principle of corrective justice, where all parties have equal rights to seek redress. Tighter supervision should be implemented by OJK to prevent legal violations while ensuring equity in the restoration of rights and the effectiveness of the legal system in dealing with disputes in the capital market.